Comparative analysis of combined spinal epidural and spinal plus single shot femoral nerve block as post-operative analgesia in total knee replacement surgery - Mahure, Shirish Mohan; Chavan, Ramprasad Pralhad; Dedhiya, Kalyanji; Amle, Dnyanesh Balkrishna (Asian Journal of Medical Sciences, 2021)
Background: Effective anaesthesia is required to overcome complications of epidural anaesthesia and relieve the patients undergoing lower limb surgeries such as total knee replacement from severe pain. Aims and Objective: The current study was aimed to study combined spinal- epidural anaesthesia (CSEA) and spinal plus single shot femoral nerve block (SSFNB) for post-operative analgesia in total knee replacement surgeries. Materials and Methods: This prospective observational and randomized study included 60 subjects undergoing Total knee replacement which were randomized into two groups and administered combined spinal epidural block and single shot femoral nerve block as per standardised protocol for post-operative pain management. Pain as per visual analogue scale and need of rescue analgesia and other haemodynamic parameters were compared between two groups and at different time interval. Result: Two study groups were found to be matched for age, gender, weigh, height and ASA grading. SSFNB group showed significantly high VAS score at 6 Hr, need for rescue analgesia, compared to CSEA group. CSEA group had significantly high number of patients with motor block. significant difference in the variation of pulse rate was observed within both the groups. Significantly higher systolic blood pressure at 6h, 12h, 24h and 36h., diastolic blood pressure at 6h, 24h and 48h and in mean arterial pressure at 6h, 24h and 36 h was observed in SSFNB group compared to CSEA group. Conclusion: We concluded that, patients undergoing total knee replacement show better analgesia and hemodynamic stability with CSEA in comparison to SSFNB, but at the cost of more motor blockade on non-operative limb and delayed recovery.